The “mad cow disease”. A bioethics’ issue in the new settings - Vera Lara, José Miguel (Acta Bioethica, 2001)
Bovine Spongiform Encephalopathy ("mad cow disease") appears in a moment and in a context that highlights the achievements and failures of biotechnology. The reality of globalization evidences the need to set limits to a technoscience viewed as unlimited because of its breakthroughs. Livestock industry profitability versus public health have been placed on the balance. Mad cow disease is an unforeseen stumble, since it was something unexpected in a system considered as perfect. This fact has disclosed a fissure that is contextual for the moment. Human contagion is a red alert, a warning sign that must be taken into account. Crisis is just in its initial stage.